Peculiarities of Non-Stationary Temperature Distribution of Optical Non-Transparent Anisotropic Thermoelement at Impulse Ray Excitement - Gutsul, I. V.; Gutsul, V. I. (Physics and Chemistry of Solid State, 2015)
The solutions of the non-stationary equation of thermoconductivity for the optical non-transparent thermoelement at impulse ray excitement are presented in the paper for two-time ranges: when the ray current falls (0<t<tau) and when it stops (t<tau). It is shown that the behavior of temperature distributions essentially depends on the relationship between the impulse duration (tau) and relaxation time (tau0) of temperature shifts over the whole volume of anisotropic thermoelement, arising at the impulse ray excitement. The non-stationary temperature distributions are studied for the long, short and middle impulse excitement.